KOMUNIKASI VISUAL PADA KEMASAN BESEK MAKANAN OLEH-OLEH KHAS BANYUMAS - Evelyne Henny Lukitasari (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article discusses the bamboo baskets used for packaging traditional food from Banyumas and the meaning of the visualcommunication on the basket packaging of this food through a semiotic approach. The basket packaging is given a criticalanalysis with an interactional analysis using a semiotic approach. The interactional analysis is used to obtain a connectionbetween all the data collected using ethical research or based on the data found in the library or based on the knowledge andopinions of the researcher. The goal of the analysis of visual communication on the bamboo baskets used for packagingtraditional food from the Banyumas area is to discover the existence of the basket packaging of this food and to analyze andgain an understanding of the visual communication on the baskets used for packaging traditional food from Banyumas. Thebenefit of the analysis of visual communication on basket packaging of traditional food from Banyumas is that it will provideinformation about the visual communication on this packaging that can be used as input and as a reference for the governmentwhen determining policies regarding the packaging of traditional Banyumas food. The character of the brand element on thesix types of basket packaging of traditional Banyumas food that were studied shows the denotative meaning regardinginformation about the name of the food, the taste, the weight, the expiry date, the address of the place selling the food, as wellas other information, through the element of layout, consisting of the colour, logo, illustration, and typography. The connotativemeaning reflects the desires, hopes, and aims of the producers regarding the sale of their food.Keywords: brand, visual brand, semiotics